Efficacy and Safety of Omadacycline in Intravenous Drug Using (IVDU) and Hepatitis C-Positive (HCV+) Patients with Acute Bacterial Skin and Skin Structure Infections (ABSSSI): A Subgroup Analysis from the OASIS Trial. (4th October 2017) - Ohl, Christopher; Cure-Bolt, Nancy; Chitra, Surya; Tzanis, Evan; McGovern, Paul
Abstract: Background: Skin infections are common in IVDU patients. HCV+ patients often have abnormal liver enzymes and transaminitis is a known tetracycline adverse effect. Omadacycline (OMC), is a novel, broad-spectrum aminomethylcycline related to tetracyclines. In OASIS, a phase 3 ABSSSI study, intravenous (IV)-to-oral OMC was non-inferior to IV-to-oral linezolid (LZD). Here, we report efficacy and safety of OMC vs. LZD in IVDU and HCV+ patients from OASIS. Methods: 655 patients were randomized 1:1 to OMC 100 mg IV q12h × 2 doses then 100 mg IV q24h, or to LZD per label. After ≥ 3 days' IV therapy, patients could transition to oral OMC 300 mg q24h or oral LZD. Total treatment duration was 7–14 days. Primary endpoint was early clinical response (ECR) assessed in the modified intent to treat (mITT) population. Secondary endpoints were clinical response at post-treatment evaluation (PTE) in the mITT and clinically evaluable (CE) populations. 322 patients were IVDU and 323 were non-IVDU; 168 were IVDU/HCV+ while 305 were non-IVDU/HCV-negative (–). Results: ECR rates with OMC and LZD were similar in IVDU vs. non-IVDU patients and IVDU/HCV+ vs. non-IVDU/HCV– patients. PTE responses with OMC in non-IVDU patients were significantly higher vs. LZD. At PTE, OMC clinical success was lower in IVDU/HCV+ vs. non-IVDU/HCV– patients. All subgroups displayed a generally similar and well-tolerated safety profile. There were no major differences in liver function tests across the subgroups and no OMC IVDU patient had a post-baseline ALT/AST greater than 3x the upper limit of normal. Conclusion: IV to once-daily oral OMC was effective, safe, and well-tolerated for treating ABSSSI irrespective of IVDU or HCV status. Disclosures: N. Cure-Bolt, Paratek Pharmaceuticals: Employee and Shareholder, Salary; S. Chitra, Paratek Pharmaceuticals: Employee and Shareholder, Salary; E. Tzanis, Paratek Pharmaceuticals: Employee and Shareholder, Salary; P. McGovern, Paratek Pharmaceuticals: Employee and Shareholder, Salary